Implementation of Halal Product Guarantee in Dental Health Services in Islamic Hospital - Rahadian, Bayu; Hakim, Nurrachma; Kurniawan, Andre; Putri, Andin Rahmania; Adienda, Claritasha (International Journal of Human and Health Sciences (IJHHS), 2019)
Islamic hospitals have the responsibility for implementing sharia service standards in all aspects, including in dental health services. As consumers, Muslim patients demand a certainty of halal status on materials used in dental treatment. Many reports said that the materials are not all halal-guaranteed. Islamic hospitals are expected to meet the needs of the Muslim community for sharia-compliant dental health services. For Muslim patients, the halal status of medical products is clearly a concern. Therefore it is necessary to protect Muslim patients when they want to use dental health services in Islamic hospitals. This is in line with a number of regulations, such as the law on hospital, the law on consumer protection, and the law on halal product guarantee. The halal product guarantee is important and feasible to be implemented to dental health services in Islamic hospitals because of the demands of Islamic hospitals to apply sharia standards and the needs of Muslim patients. International Journal of Human and Health Sciences Vol. 03 No. 02 April’19. Page: 54-57